Microbiological Chitosan: Potential Application as Anticariogenic Agent - Stamford, Thayza Christina Montenegro; Stamford-Arnaud, Thatiana Montenegro; Cavalcante, Horacinna Maria de Medeiros; Macedo, Rui Oliveira; Campos-Takaki, Galba Maria de (IntechOpen, 2013)
None